Análise de indicadores da produção científica, tecnológica e artística do Instituto Federal de Sergipe - IFS - Silva, Maria Aparecida da Conceição Gomes da (2016)
This research intends to analyze a set of educational indicators and scientific, technological and artistic production of research groups linked to the Federal Institute of Sergipe (IFS), in order to offer some useful clues for the definition of priorities to be implemented by an institutional policy Of science and technology in which research, teaching, extension and innovation actions are integrated and articulated with local, regional and national scientific and technological development. The scope of the research is structured around the following axes: (i) survey of IFS human resources; (Ii) characterization of research groups; (Iii) definition of the educational profile of the participants of the research groups; (Iv) survey of the scientific, technological and innovation productivity of group leaders; (V) identification of the institutional partnerships developed between the IFS and the productive sector.This is a quantitative / qualitative and analytical / descriptive research that used information extracted from lattes curricula and from the Directory of Brazilian Research Groups (DGP), from the Lattes / CNPq platform, as a secondary source of data that were collected by Instrument (questionnaire) composed of quantitative and qualitative variables. The sample consisted of updated and certified research groups from IFS and their respective leaders. The resulting data of the quantitative variables are presented in tables, whereas those generated from the qualitative variables are analyzed in light of the Content Analysis. In this way, it seeks to give visibility to the challenges and advances faced by the IFS research groups in order to contribute to the development and strengthening of an institutional science and technology policy.According to the results, it was verified that the IFS has 52 certified and updated research groups, 205 research lines and 70 group leaders distributed as follows: undergraduate (02), master's degree (25), doctorate (40) and Postdoctoral (03), working in the areas of arts and letters, biological sciences, human sciences, agrarian sciences, applied social sciences and exact sciences and earth. The groups have partnerships with eleven (11) institutions, most of them (81%) concentrated in the states of the Northeast region. Regarding the sector of activity, the majority (45%) work in higher education. Regarding the legal nature, only three (03) companies belong to the private sector, which corresponds to (27%). With regard to the generic form of remuneration, partnership prevails without the transfer of resources of any kind, involving exclusively risk relationships. This study shows the need to formulate an institutional science and technology policy capable of encouraging the overcoming of gender inequalities, supporting the internalization of research in the state of Sergipe and bringing the IFS institution closer to other public and private institutions in order to better Contribute to the technological development and, consequently, economic and social state.